[OA086] An innovative gynecological HDR brachytherapy applicator system for treatment delivery and real time verification. (August 2018) - Romanyukha, Anna; Carrara, Mauro; Petasecca, Marco; Al-Salmani, Tebarak; Cutajar, Dean; Cerrotta, Annamaria; Fallai, Carlo; Pignoli, Emanuele; Rosenfeld, Anatoly
Abstract : Purpose: To develop, calibrate, and test an innovative prototype of a vaginal applicator that can be used for dose delivery and real-time source position and dwell time verification in high dose rate (HDR) 192 Ir brachytherapy (BT). Methods: The applicator prototype is modeled based on a multichannel vaginal applicator that is 30 mm in diameter and contains seven peripheral and one central channel(s). Three p-type epi diodes with an active area of 1.5 × 1.5 mm 2 are attached to the applicator, selected due to their efficiency in the measurement of high-energy photons associated with the 192 Ir source. The diodes have been placed around the upper 30-mm region of the applicator, encompassing the most clinically relevant region for HDR BT treatments. The readout system is an AFE and FPGA system capable of 100  μ s online readout for up to four diodes at a time. The ad hoc detectors and electronics have been all developed at CMRP. A prototype of the system has been characterized to establish the method of source localization and dwell time measurement, and then tested in phantom to evaluate its performance for dwell position and time verification. Two random source positions within the seven peripheral channels of the applicator were tested, with dwell times of 5 and 10 s. Results: The characterization of the system showed no significant dependence on radiation intensity for a range of air Kerma strengths between 13 and 34 mGy · m 2 · h − 1 . Following characterization, the system has demonstrated the ability to resolve the HDR BT source position in the arbitrary treatment plan for a range of 0–30 mm along the applicator, encompassing the first 13 dwell positions of 2.5 mm step size. The average absolute positional and dwell time discrepancies were recorded as 0.3  ±  0.2 mm and as 0.3  ±  0.1 s with a maximum of 0.6 mm and 0.6 s, respectively. Conclusions: The proposed intracavitary HDR BT applicator system has demonstrated the ability to simultaneously deliver and verify the BT treatment in real-time with sub-mm and sub-second accuracy. New diodes will soon be implemented to increase the range of positional and dwell time sensitivity.